Emerging conceptions of work, management and the labor market - Vallas, Steven P. 1951- (Emerald Publishing Limited, 2017)
Economic institutions are undergoing radical transformations, and with these has come a reconfiguration of labor market institutions, managerial conceptions of work, and the nature of authority and control over employees as well. This volume addresses a wide array of questions to better understand these dramatic changes.
Keywords: Management.; Labor market.; elektronické knihy; electronic books